New media usage and youth participation - Ali Salman,; Mohd Azul Mohamad Salleh,; Normah Mustaffa,; Mohd. Nor Shahizan Ali, (Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2015)
The Internet is considered a huge development in human civilization. It is literally considered as a practical key or essential to human development and social advancement causing massive innovation in the world. Over the years, the advent of new media has permeated most aspects of our lives, especially that of the young generation. It is against this background that this paper aims to analyse the present use of the new media by youth to gauge their usage in relation to participation and nation building. This study is a country wide survey covering Peninsula and East Malaysia. For sampling purposes the country is divided into six zones. A survey research using questionnaire as instrument was used to obtain data. Prior to the actual survey, a pilot study was first conducted. Some 1182 respondents’ age between 18 and 25 were randomly sampled from the six zones and selection was based on ethnic ratio. The data was analysed descriptively and inferentially using SPSS 20.0. From the results, majority of the respondents, 89% are social media users having a social media account. A discouraging trend with regard to participation is the very low level of giving comments on general societal issues ranging from social issues, the environmental to politics. As it is now, the youth are more inclined to using the new media for entertainment and social networking. It is time to use the new media to engage with community leaders and politicians and comment on issues related to nation building.